Microsatellite markers in aquaculture: application in fish population genetics (2013)
Microsatellites or Simple Sequence Repeats (SSRs) represent an abundant source of genetic markers which are highly abundant and dispersed evenly throughout eukaryotic genomes. They have become the markers of choice for a wide range of applications in population genetic, conservation and evolutionary biology. Microsatellites represent ideal molecular markers because they have multiple alleles which are highly polymorphic among individuals. Polymorphism is achieved by having variable numbers of tandem repeat motifs resulting in size variation which can then be visualized by PCR with pairs of locus-specific flanking primers, followed by electrophoresis of the amplification product. Microsatellite motifs occurs once every 10kb in fishes. They are inherited in a co-dominant fashion, and are fast and easy to assay. They are co-dominant in nature with high levels of polymorphism and can reproduce very well. Hence, giving better information than the dominant marker .This makes them a choice maker for estimating population structure and genetic diversity.